The Chloroplast Reactive Oxygen Species-Redox System in Plant Immunity and Disease - Kuźniak, Elżbieta; Kopczewski, Tomasz (Frontiers in Plant Science, 2020)
Pathogen infections limit plant growth and productivity, thus contributing to crop losses. As the site of photosynthesis, the chloroplast is vital for plant productivity. This organelle, communicating with other cellular compartments challenged by infection (e.g., apoplast, mitochondria, and peroxisomes), is also a key battlefield in the plant–pathogen interaction. Here, we focus on the relation between reactive oxygen species (ROS)—redox signaling, photosynthesis which is governed by redox control, and biotic stress response. We also discuss the pathogen strategies to weaken the chloroplast-mediated defense responses and to promote pathogenesis. As in the next decades crop yield increase may depend on the improvement of photosynthetic efficiency, a comprehensive understanding of the integration between photosynthesis and plant immunity is required to meet the future food demand.